A new Early Jurassic dinosaur represents the earliest-diverging and oldest sauropodomorph of East Asia - Ya-Ming Wang; Qian-Nan Zhang; Yan-Chao Wang; Huan Xu; Jianbo Chen; Zhuo Feng; Xing Xu; Tao Wang; Hai-Lu You (Scientific Reports)
Abstract A new dinosaur assemblage from the Lower Jurassic at Wande Town, Wuding County, Yunnan Province, China is discovered recently. Here a new sauropodomorph from this site, Wudingloong wui gen. et sp. nov., is described on the basis of a partial skeleton. Wudingloong is different from other non-sauropodiform sauropodomorphs particularly in having an ascending ramus of the maxilla excavated by triangular antorbital fossa, distinct ventral keel on the middle cervical centra, a slender humerus with a flat and low humeral head, a gracile metacarpal V with the proximal end as wide as the distal end, and a large and robust ungual of manual digit I. Wudingloong was excavated from the lowest Lower Jurassic Yubacun Formation, which is the lowest dinosaur bone bed in East Asia. Both the phylogenetic analysis and stratigraphic horizon indicate that Wudingloong represents the earliest-diverging and stratigraphically oldest sauropodomorph dinosaur discovered in East Asia so far. The discovery of this new taxon provides further evidence that the southwestern China sauropodomorph assemblage is one of the most taxonomically diverse and morphologically disparate in the pre-Toarcian Early Jurassic worldwide, represented by various taxa from near the base of the Massopoda to non-sauropodan sauropodiforms.